2014
DOI: 10.1186/2193-1801-3-641
|View full text |Cite
|
Sign up to set email alerts
|

Selection of high temperature and salinity tolerant Trichoderma isolates with antagonistic activity against Sclerotium rolfsii

Abstract: Trichoderma isolates were collected from varied agro-climatic zones of India and screened for high temperature and salinity tolerance. Among all the isolates tested, T. asperellum, TaDOR673 was highly tolerant to heat shock of 52°C with a mean spore count (log c.f.u/ml) of 4.33. The isolate after recovery from heat shock possessed higher germination rate and biomass production compared to its wild counterpart, upon prolonged exposure to 37°C. Under stress, TaDOR673 accumulated >15% of trehalose and >5% of mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…asperellum (belonging to the Viride Clade and more abundant in the coast ecosystem in this study, Fig. A) was able to tolerate salt stress at 1 M NaCl compared with about 0.6 M NaCl of seawater (Poosapati et al ., ), which is a possible reason for the enrichment of the Viride Clade in coastal ecosystems in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…asperellum (belonging to the Viride Clade and more abundant in the coast ecosystem in this study, Fig. A) was able to tolerate salt stress at 1 M NaCl compared with about 0.6 M NaCl of seawater (Poosapati et al ., ), which is a possible reason for the enrichment of the Viride Clade in coastal ecosystems in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…This indicates that Trichoderma was able to germinate above the optimum temperature. The results of research by Poosapati et al (2014) showed that the Trichoderma asperellum TaDOR673 fungi isolate was highly tolerant to 52C high temperature, and the fungi was still able to produce fairly dense conidial and higher conidial germination compared to other isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Conidial germination of various antagonistic fungi is strongly influenced by changes in temperature and ultraviolet light exposure. According to Poosapati et al (2014) conidia of Trichoderma spp from different agro climatic zone of India reduced their ability to germinate at temperature 37°C except for T. asperellum-TaDOR673. This fungi isolate was highly tolerant at high temperature 52°C, and was still able to produce fairly dense conidial and higher conidial germination compared to other isolate.…”
Section: Introductionmentioning
confidence: 99%
“…Many Trichoderma species are capable of withstanding low and high temperatures. Two isolates of Trichoderma from soil samples collected from various regions of India withstood a heat shock of 52 • C and prolonged exposure to temperature of 37 • C while maintaining high tolerance to salinity [117]. Information from this study and others may be used to build a resilient tool that combines Trichoderma species based on their temperature and salinity response.…”
Section: Plant Pathogens and Climate Change In The Sw Usmentioning
confidence: 92%